ANALYSIS OF THE EFFECT OF NON-FINANCIAL MOTIVATION ON EMPLOYEE PERFORMANCE CV. BERTA LESTARI ANGGANA - Oktaviani Dwi Saputri; Fenty Fauziah; Joko Sabtohadi (Jurnal Scientia, 2022)
This study aims to analyze and determine the effect of Non-Financial Motivation on Employee Performance at CV. Berta Lestari Anggana. This research uses quantitative research. The sampling technique used is Non Probability Sampling using the Saturated Sampling (census) technique. The sample of this study amounted to 40 employees CV. Berta Lestari Anggana. Data were collected through questionnaires and tested with data instrument tests, classical assumption tests, simple linear regression analysis, hypothesis testing and coefficient of determination tests. All these tests were carried out using the SPSS (Statistical Product and Service Solutions) 26 for Windows program. The results showed that non-financial motivation had a positive and significant effect on employee performance at CV. Berta Lestari Anggana.